Tarımın faizsiz araçlarla finansmanı - Şahin, Bertaç Şakir (My University, 2019)
Dini, ekonomik ve sosyal sebeplerle yirminci yüzyılın ikinci yarısında faizsiz finansman araçları ortaya çıkmıştır. İslamiyet’in erken dönemindeki uygulamalar esas alınarak ve geleneksel finansman araçlarının İslami hükümlerle uyumlaştırılması ile oluşturulan faizsiz finansman araçları, geleneksel finansman araçlarıyla birlikte tasarrufların yatırımlara dönüşmesine yardımcı olurken dini hassasiyetleri sebebiyle finansal piyasalarda yer almayan yatırımcılar için iyi bir alternatiftir. Faizsiz finansman araçlarının etkin bir şekilde kullanılacağı alanlardan biri tarımsal üretimdir. Faizsiz finansman araçları, yapısı itibariyle tarımın finansmanı için uygun özelliklere sahiptir. Tarımsal üretimin finansmanı, tarımın kendine has yapısı ve sektörün içinde barındırdığı riskler sebebiyle üzerinde önemle durulması gereken bir konudur. Sektörün her kesimine ulaşabilmek ve tarımsal üretimin karakterine uygun hareket edebilmek adına faizsiz finansman araçlarının tarımın finansmanında kullanılması gerekmektedir. Bu tezde tarımın dünyadaki ve Türkiye’deki durumuna değinilip, tarımın finansmanında kullanılan mevcut finansman yöntemlerinden bahsedildikten sonra yeni bir alternatif olarak faizsiz finansman araçları tanıtılmaya ve uygulamaya yönelik öneriler sunulmaya çalışılmıştır. Her bir finansman aracına ilişkin muhasebe kayıtları da yapıldıktan sonra tezin son bölümünde faizsiz finansman araçlarının doğru bir şekilde uygulanabilmesi konusunda önem taşıyan hukuki düzenlemeler incelenmiştir. Tezde faizsiz finansman araçlarının, emek yoğun ve düşük sermaye ile çalışan tarım üreticileri için uygun finansman araçları olduğu sonucuna ulaşılmıştır. Ancak Türkiye’deki faizsiz finansman sistemiyle tarımsal üretimde etkin bir faizsiz finansman mümkün değildir. Bu sebeple tezde sunulan önerilere uygun bir faizsiz finansman organizasyonunun kurulması önem taşımaktadır. Ayrıca faizsiz finansman mevzuatı geleneksel finansman ile faizsiz finansmanın arasındaki farkı ortaya koyma ve finansman araçlarının uygulanmasına ilişkin yol gösterme konularında eksiktir.

In the second half of the twentieth century, interest-free financing instruments were developed for religious, economic and social reasons. The interest-free financing instruments which On the basis of early Islamist practices and the harmonization of traditional financing instruments with Islamic provisions, are a good alternative for investors who do not participate in financial markets due to their religious sensitivity while helping to transform savings into investments with traditional financing instruments. Agricultural production is one of the areas where interest-free financing instruments can be used effectively. Interest-free financing instruments have appropriate characteristic features for the financing of agriculture. The financing of agricultural production is an issue that needs to be emphasized due to the unique structure of agriculture and the risks inherent in the sector. In order to be able to appeal to all parts of the sector and to act in accordance with the character of agricultural production, interest-free financing instruments should be used in the financing of agriculture. In this thesis, situation of agriculture in world and in Turkey mentioned and after the mention about existing financing methods used financing agriculture, new alternative to interest-free financing instruments have been tried to be introduced and offered suggestions for implementation. After the accounting records about to each financing instrument have been made, In the last part of the thesis, the legal regulations which are important for the correct application of interest-free financing instruments were examined. In the thesis, it was concluded that interest-free financing instruments are suitable for agricultural producers who working with labor intensive and low capital. However, with interest-free financing system in Turkey, efficient financing agriculture with interest free instruments is not possible. For this reason, it is important to establish an interest-free financing organization in accordance with the proposals presented in the thesis. Interest-free financing legislation is also lacking in the allocation of traditional financing and interest-free financing and information about the implementation of financing instruments.
Keywords: Agriculture; Faizsiz Finansman; Financing Agriculture; Finans; Interest Free Financing; Tarım; Tarımın Finansmanı Finance